Behavior Based Safety Implementation for Reducing Workplace Accident Risk: Penerapan Keselamatan Berbasis Perilaku untuk Mengurangi Risiko Kecelakaan Kerja - Aljabaru P.P, M.Rafly; Putra, Boy Isma (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Workplace safety is a critical aspect in industrial operations, particularly in reducing occupational accidents caused by unsafe behaviors. Specific Background Behavior Based Safety (BBS) is widely applied to identify and control unsafe actions and improve worker safety performance. Knowledge Gap However, limited studies integrate behavioral analysis with systematic evaluation of safety practices in specific industrial settings. Aims This study aims to analyze unsafe behavior and implement Behavior Based Safety to reduce workplace accident risks. Results The findings indicate that unsafe actions, lack of personal protective equipment usage, and insufficient safety awareness are dominant factors contributing to accidents. The implementation of BBS highlights improvements in safety awareness and behavior monitoring. Novelty This study emphasizes the integration of behavioral observation and safety evaluation within a structured BBS framework. Implications The results provide practical recommendations for improving safety culture, strengthening supervision, and reducing accident risks in industrial environments. Keywords: Behavior Based Safety, Workplace Safety, Unsafe Action, Safety Behavior, Accident Prevention Key Findings Highlights Unsafe behavior identified as primary contributor to incidents Protective equipment compliance remains inconsistent among workers Safety monitoring supports improved workplace awareness